POTENSI ANTIJAMUR MINYAK ATSIRI DAGING BUAH PALA (Myristica fragrans Houtt) ASAL PULAU SANGIHE PADA Malassezia furfur - Nahor, Evelina Maria; Rindengan, Elvie Rifke; Maramis, Rilyn Novita; Rintjap, Djois Sugiaty; Soenjono, Steven Jacob; Kalonio, Donald Emilio (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Pityriasis versicolor or tinea versicolor is a skin disease caused by the fungus Malassezia furfur. Nutmeg fruit pulp essential oil contains myristicin compounds that have potential as antimicrobials. The purpose of this study was to determine the antifungal activity of nutmeg fruit pulp essential oil (Myristica fragrans Houtt) from Sangihe Island against Malassezia furfur fungus using the Agar Diffusion and Vapor Phase Test methods. The samples used were nutmeg fruit taken directly from the garden, isolated nutmeg fruit pulp essential oil using the water vapor distillation method. The antifungal activity test for Malassezia furfur used the Agar Diffusion method, using nutmeg oil with concentrations of 20%, 40%, 60%, 80% and 100%, while the antifungal test with the Vapor Phase Test method used nutmeg oil with volumes of 0 μL, 10 μL, 20 μL, 40 μL, 80 μL and 100 μL. Observations were made by measuring the diameter of the clear zone after 24 hours of incubation. The results showed that essential oils of nutmeg fruit flesh at concentrations of 20%, 40%, 60%, 80% and 100% using the Agar Diffusion method were able to inhibit the growth of Malassesia furfur fungus, while with the Vapor Phase Test method the antifungal activity of essential oils of nutmeg fruit flesh was at test volumes of 40 μL, 80 μL and 100 μL.